Thermal flow sensor for ultra-low velocities based on printed circuit board technology - Nguyen, N T (2014)
This paper presents a new thermal flow sensor for ultra-low velocities. The sensor was fabricated with the standard printed circuit board (PCB) technology. The technology and the simple sensor design would reduce costs in fabrication and packaging. A one-dimensional analytical model is presented in order to understand the working principle and to optimize the sensitivity. A two-dimensional finite element analysis (FEA) model is also presented. The paper describes the experimental investigations of the temperature field around a heater under the influence of forced convection. The experimental and theoretical optimization results lead to the design of the PCB sensor whose characteristics are presented at the end of the paper. With the current calibration facility, the sensor is able to measure air flow velocities less than 80 mm s-1.